Antimony‐based nanomaterials for high‐performance potassium‐ion batteries. Issue 2 (2nd June 2020) - Gao, Hong; Guo, Xin; Wang, Shijian; Zhang, Fan; Liu, Hao; Wang, Guoxiu
Abstract: Potassium‐ion batteries (PIBs) present great potential for large‐scale energy storage applications owing to their high energy density and the abundance of potassium reserve. However, the large radius of K + and super‐reactive metallic nature of potassium make it difficult to realize electrochemically reversible storage with most conventional electrode materials. Currently, it remains a great challenge to develop appropriate anode materials with high specific capacities, long cycle life, and low cost for PIBs. Antimony‐based materials are recognized as a promising anode candidate because of their high theoretical capacities, appropriate potassiation potential, and relatively low cost. Herein, we review the recent progress of antimony‐based anode materials for PIBs, including metallic antimony, antimony‐based alloys, antimony chalcogenides, and composite combinations. Meanwhile, this review also focuses on the electrochemical reaction mechanisms, strategies for design and synthesis of electrode materials, and the advances of electrolyte modulation and electrode formulation. Finally, we present the critical challenges to be addressed and perspectives for ways forward to promote the development of PIBs. Abstract : Antimony‐based materials, including metallic antimony, antimony‐based alloys, antimony chalcogenides, and their composite combinations have attracted considerable interests in potassium‐ion batteries. In this review, we summarize the advances and challenges of antimony‐based anodes for potassium storage and present our perspectives for ways forward to promote development of the high‐performance anode materials.